Urgensi Batas Kewajiban Staff Administrasi Notaris Dalam Menjaga Kerahasiaan Akta Dari Perspektif Asas Kepastian Hukum - Melina, Putu Jelsi; S., Pande Yogantara (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
The purpose of this article is to explore the legal relationship between notaries and their employees in the provisions of the Employment Law as well as the limits of the obligations of notary administrative staff in maintaining the confidentiality of the contents of deeds, which in this case has not been fully regulated clearly regarding the extent of the provisions regarding the obligations of notary staff in maintaining confidentiality. Deed. This journal article is a type of normative legal research which is supported by a conceptual approach and a case approach. And this research applies descriptive analysis techniques to legal materials. Research findings show that the relationship between a notary and a notary employee can be categorized as an employment relationship in accordance with the provisions of Article 1 point 15 of the UUK where the Notary is the employer in accordance with the provisions of Article 1 Number 4 of the UUK which is based on a work agreement in accordance with the provisions of Article 1 number 14 of the UUK , as well as regarding the limitations of Notary Staff in maintaining the confidentiality of deeds which results in a vacuum in norms, because there are no provisions regarding the extent of the notary staff's obligation to maintain the confidentiality of the Deed itself.